Reel politik - Gelgud, Nathan, 1978-; Forsman, Charles; Mendes, Melissa; Thurber, Matthew (Drawn & Quarterly, 2025)
"A specter is haunting the cinema. A contrarian crew of small-town theater employees trade quips about directors, film criticism, and contemporary moviegoing, but underneath their banter and clashes with customers, an idealogy beings to take shape."--